Strategic Education Marketing: Analyzing the Implementation of the 7P Marketing Mix in Indonesian Islamic Universities - Ali Marzuki Zebua; Kasful Anwar Us (STAI Hubbulwathan Duri, 2025)
The competition in Indonesia’s higher education sector is intensifying, particularly between State Islamic Higher Education Institutions (PTKIN) and Public Universities (PTU). To remain competitive, institutions like IAIN Kerinci must implement effective marketing strategies. This study examines the application of the 7Ps marketing mix at IAIN Kerinci to enhance its institutional competitiveness. This research employed a qualitative library research method, using the 2021 IAIN Kerinci Self-Evaluation Report (LED) as the primary data source. The analysis was conducted using the 7Ps marketing framework—product, price, place, promotion, people, process, and physical evidence—and was complemented by a SWOT analysis to assess implementation effectiveness. Additionally, interviews with selected respondents were conducted to enrich the findings. IAIN Kerinci has implemented a well-rounded marketing strategy. Key initiatives include diversification of academic programs, soft skill development, and provision of career and counseling services. Tuition is aligned with perceived value, and the campus’s strategic location enhances accessibility. Continuous professional development for faculty and staff ensures high competence. Service delivery is structured and supported by adequate physical infrastructure. Promotional efforts involve partnerships with local schools, public engagement, and digital outreach through social media. The application of the 7Ps strategy has significantly improved educational service quality and institutional appeal. Continued refinement and adaptation of this strategy are recommended to address evolving challenges in the higher education landscape.